2009
DOI: 10.1007/s12274-009-9003-1
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Na0.44MnO2 nanowires via stress-induced splitting of birnessite nanosheets

Abstract: High aspect ratio Na 0.44 MnO 2 nanowires with a complex one-dimensional (1 D) tunnel structure have been synthesized. We found that the reaction went through layered birnessite nanosheet intermediates, and that their conversion to the fi nal product involved splitting of the nanosheets into nanowires. Based on our observations, a stress-induced splitting mechanism for conversion of birnessite nanosheets to Na 0.44 MnO 2 nanowires is proposed. The fi nal and intermediate phases show topotaxy with 001 f // 020 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 23 publications
1
46
0
Order By: Relevance
“…1(a)) indicated that the shape of the resulting nanocrystals was almost octahedral, but they are tetragonally distorted due to the Jahn-Teller effect on Mn 3+ ions [29]. Edge-shared [MnO 6 ] octahedral units [8,30,31] originate from the reaction at the nonbridging hydroxyl groups of adjacent micellar particle surfaces and form a chemical bond. Their construction results in agglomeration of most of the nanocrystals.…”
Section: Resultsmentioning
confidence: 99%
“…1(a)) indicated that the shape of the resulting nanocrystals was almost octahedral, but they are tetragonally distorted due to the Jahn-Teller effect on Mn 3+ ions [29]. Edge-shared [MnO 6 ] octahedral units [8,30,31] originate from the reaction at the nonbridging hydroxyl groups of adjacent micellar particle surfaces and form a chemical bond. Their construction results in agglomeration of most of the nanocrystals.…”
Section: Resultsmentioning
confidence: 99%
“…in a basic or dilute acidic medium or by electrochemical conversion from Mn 3 O 4 thin films [21,[24][25][26][27]. In particular, hydrothermal treatment of Mn 2 O 3 or Mn 3 O 4 powders in NaOH solution leads to the production of Na-bir nanobelts [26], or tunnel structure Na 0.44 MnO 2 nanowires [27].…”
Section: The Formation Of Layered Birnessite-type Mno 2 Nanowiresmentioning
confidence: 99%
“…A second hydrothermal treatment was adopted to investigate the stability of birnessite nanowires in NaOH solution [27]. The birnessite nanowires were mixed again with 20 mL of 6 M NaOH solution and heated at 180 • C for another 72 h. The XRD profile (Fig.…”
Section: The Formation Of Layered Birnessite-type Mno 2 Nanowiresmentioning
confidence: 99%
“…The FFT pattern of the nanodisc shows six-fold symmetry, whereas the whisker shows rectangular symmetry. These indicate that the nanodiscs and whiskers are Na-birnessite and Na 0.5 MnO 2 , respectively [14]. In Fig.…”
Section: Growth Mechanismmentioning
confidence: 80%
“…Na 0.44 MnO 2 was early synthesized via high temperature solid state reaction of stoichiometric Na 2 CO 3 and Mn 2 O 3 [9,12,13]. Recently, Na 0.44 MnO 2 nanowires with high aspect ratio have been synthesized using hydrothermal method [7,14]. The size of the crystals obtained by the above methods is small with diameters below 500 nm.…”
Section: Introductionmentioning
confidence: 99%